CANNABINOIDS IN CHRONIC PAIN MANAGEMENT: EFFICACY, SAFETY, AND THE CONTROVERSIES SURROUNDING MEDICAL MARIJUANA – A REVIEW OF CURRENT EVIDENCE - Szymon Szabelski; Adam Solarz; Joanna Kryślak; Maciej Sokołowski; Karolina Oskroba (International Journal of Innovative Technologies in Social Science, 2025)
Chronic pain is a highly complex phenomenon in terms of both etiology and clinical presentation. Due to its prolonged duration, it significantly impairs the functioning of many patients. In the era of modern analgesic therapy, increasing hope is placed on the use of cannabis-based preparations. Cannabinoids, primarily THC and CBD, acting on the endocannabinoid system, exhibit analgesic, anti-inflammatory, and even neuroprotective effects. They have a relatively favorable safety profile for patients, and their adverse effects typically do not interfere with patients’ daily functioning. However, due to the variable efficacy reported in previous studies, the potential placebo effect, and short-term observations, a larger number of well-designed, double-blind randomized controlled trials are required to precisely determine the role of cannabinoids in chronic pain management.